Phenology of nesting marine turtles in the Cayman Islands - Liliana P. Colman; Jane L. Hardwick; Timothy J. Austin; Janice M. Blumenthal; Gina Ebanks-Petrie; Brendan J. Godley; Lorri D. Lamb; Alejandro Prat-Varela; Joseph Roche-Chaloner; Annette C. Broderick (PLoS ONE, 2025)
Climate-driven shifts in the phenology of species are altering ecosystems worldwide and have been documented in many species, including marine turtles. We present a 26 year analysis of population trends and nesting phenology for green ( Chelonia mydas ) and loggerhead ( Caretta caretta ) turtles in the Cayman Islands and show that although the onset of nesting has advanced for both species (by 0.6 days.yr -1 for green turtles and 0.7 days.yr -1 for loggerhead turtles), the peak of nesting has not significantly changed. The end of the nesting season for green turtles has been delayed by 1.0 days.yr -1 , extending the nesting season by 1.6 days.yr -1 , whereas no significant change in season duration was observed for loggerhead turtles. Over the study period, sea surface temperature (SST) at the nesting beach has increased significantly, with warmer temperatures correlating with earlier nesting for both species. The number of nests laid each year has also increased annually by 12.4% for green turtles and 8.1% for loggerheads but did not have a significant relationship with any phenological measures (onset, peak, end, or duration of nesting season). Our data suggest that marine turtles in the Cayman Islands are shifting the onset of nesting toward cooler periods outside peak summer months however there was no change to the peak of nesting for either species. Whether this shift mitigates the impacts of rising temperatures on clutch incubation and offspring sex ratios remains unclear.